Penanganan Kepadatan Gudang PT Jasa Angkasa Semesta - Wynd Rizaldy; Johanes Kurniawan LS; Indriyati Indriyati (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of the study is to analyse and decide the factors of uncollected and dense delivery in Warehouse Line I at Soekarno Hatta airport. The study is a descriptive explorative using Cube per Order Index (COI). The data analysis used Fishbone and Focus Group Discussion (FGD). The result shows that the warehouse operator still needs to upgrade the way of handling, storing, and cargo expenditure by coordinating with other related institutions.